2019
DOI: 10.1371/journal.pone.0219057
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-rater reproducibility of ultrasound imaging of patellar and quadriceps tendons in critically ill patients

Abstract: Since the outset of body image reconstruction for diagnosis purposes, ultrasound has been used to investigate structural changes located in tendons. Ultrasound has clinical applications in the intensive care unit, but its utility for tendon imaging remains unknown. Thus, we aimed to determine intra- and inter-rater reproducibility of measures obtained by images generated through morphological tendon sonographic analysis recorded from critically ill patients. We designed a cross-sectional study to assess thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Intra-observer agreement was demonstrated for all tissue characterisation assessments, which included echogenicity and definition, excepting for the fat pad (layers 2–4) at the heel, and the skin (layer 1) at the lateral sesamoid foot region. We did not demonstrate inter-observer agreement for any tissue characterisation assessments, supporting the view that assessments of ultrasound tissue characteristics of musculoskeletal structures are highly subjective and variable [ 26 28 ], even when assessed by experienced sonographers using defined protocols. Therefore, these assessments have limited clinical applicability where multiple sonographers may be involved.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Intra-observer agreement was demonstrated for all tissue characterisation assessments, which included echogenicity and definition, excepting for the fat pad (layers 2–4) at the heel, and the skin (layer 1) at the lateral sesamoid foot region. We did not demonstrate inter-observer agreement for any tissue characterisation assessments, supporting the view that assessments of ultrasound tissue characteristics of musculoskeletal structures are highly subjective and variable [ 26 28 ], even when assessed by experienced sonographers using defined protocols. Therefore, these assessments have limited clinical applicability where multiple sonographers may be involved.…”
Section: Discussionsupporting
confidence: 66%
“…However, the reliability of ultrasound measurements of the plantar skin and fat pad thickness are not well documented [ 25 ]. Ultrasound can also be used to depict tissue characteristics other than thickness, but such assessments are often overlooked, including those of the plantar foot in diabetic people, due to their perceived subjectivity [ 26 28 ]. Consequently, the reliability of ultrasound for describing plantar tissue characteristics in the setting of diabetes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The highest post-race increase in QT thick was found at location placed 15 mm (Δ post-pre: 0.23 mm in the sprint and 0.17 mm in endurance track cyclists), while PT thick at 15 mm (Δ post-pre: 0.36 mm) in sprinters and 20 mm (Δ post-pre: 0.29 mm) in endurance cyclists. Castro et al ( 2019 ) have reported that the middle region of PT Thick (~20 mm) was the easiest to define and had the highest intra-rater reliability. Such increases in the tendon thickness are most likely caused by including hypoechogenicity and vascularity (Visnes et al, 2015 ; Tsui et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative interpretation of the ICC was classified as 0.00 (absent), 0.00-0.19 (poor), 0.20-0.39 (weak), 0.40-0.59 (moderate), 0.60-0.79 (good), and ≥0.80 (excellent). 35 The SEM was calculated for each ICC value as the product of SD and the square root (1−single measures ICC). The coefficient of variation (CV) was calculated by dividing the SD by the mean value of the repeated measures (CV=[SD/mean] × 100), interpreted as CV<10 (very good), 10-20 (good), 20-30 (acceptable), and CV>30 (not acceptable).…”
Section: Methodsmentioning
confidence: 99%